Covid-19 trouble at work: A comparative qualitative analysis of disclosure, sickness absence and return-to-work in the UK, the USA, Australia and Japan - Kaveri Qureshi; Jane Alice Evered; Rie Toyomoto; Anna Urbanowicz; Akiko Sawada; Lorraine Smith; Rika Sakuma Sato; Tanvi Rai (Elsevier, 2023)
This paper addresses working people's narrated experiences of managing covid-related sickness in relation to employment. Bringing together the sociology of chronic illness and disability, and of work and organisations, we contribute to understandings of Covid-19 experiences in the context of employment. We draw from interview studies of Covid-19 infection and recovery in four countries, the UK, the USA, Australia and Japan. This cross-country comparative qualitative approach enables us to suggest how macrostructural regulatory and policy environments, and micropolitical environments of social interaction and moral evaluation shape paths between disclosure to employers, sick leave-taking, recovery and return to work after Covid-19 infection. For many of our participants across the four countries - especially those lacking in job security - this path was not straightforward, entailing intertwined moral and material risks. We draw out wider real-world implications, with regards to precarious work and limited governmental safety nets, and sociological implications in terms of un-flattening our analyses of how people encounter and dispose of trouble at work.